Prevalence and Risk Factors Associated with Gastritis in Patients Visiting Royal Prima Hospital - Zulkifli Adnan; Maya Sari Mutia; Tan Suyono (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Gastritis is an inflammation of the stomach lining caused by Helicobacter pylori and can be acute or chronic. This bacteria colonizes the stomach of more than 50% of humans and causes disease. Gastritis still has a high prevalence and if left untreated can lead to serious complications, such as gastric ulcers, bleeding, and even gastric cancer. Objectives: The purpose of this study was to determine the prevalence and risk factors associated with gastritis in patients visiting Royal Prima Medan Hospital. Methods:This study was an analytic observational study with a cross-sectional design conducted on 132 patients who visited Royal Prima Hospital with gastritis complaints. Data were analyzed using univariate, bivariate (chi-square and Fisher), and multivariate analysis (logistic regression). Results: This study reported a prevalence of gastritis of 64.9%. Associated risk factors were smoking status (OR=2.20, 95% CI, 1.18-4.09); p=0.014), coffee drinking (OR=8.26 95% CI, 3.92-17.37; p<0.001), diet (OR=12.44, 95% CI, 5.75-26.87; p<0.001). Conclusions: Coffee drinking and diet are determinant factors of gastritis. Educating patients at risk of gastritis by reducing coffee consumption, quitting smoking, improving diet and other factors that can increase gastritis complications are efforts that must be made in preventing the increase in gastritis disease.